SCREENING PHYTOCHEMICAL AND ANTI-METHICILLIN RESISTANT (MRSA) ACTIVITY OF 70 % ETHANOLIC EXTRACT FROM THE STEM BARK OF ALBIZIA LEBBECK(L.) BENTH.(FABACEAE) - KANGA, Yao; Djeneb, CAMARA; Aubin, KOUASSI Kouadio; Noël, ZIRIHI Guédé (Asian Journal of Pharmaceutical Research and Development, 2018)
The emergence of multi-drug resistant strains and limitations of present antimicrobial drugs have led to continuous search for natural products as curative agents for Anti-methicillin resistantinfections. The aim of this study was to evaluate antibacterial activity of an ethanolic extract from Albizia lebbeckstem bark against Anti-methicillin resistant. Methods and Results : The methods of dissemination swab on muller-hinton agar and double dilution were used to evaluate the antibacterial activity of 70 % ethanolic extract of stem bark of Albizia lebbeck.All multi-resistant strains of Staphylococcus aureus and the reference strain (ATCC 25923) were sensitive to 70 % ethanolic extract of the stem bark of Albizia lebbeck. The MBCvary from 0,49 mg/mL to 2mg/mL. Also, the phytochemical screening of this extract revealed the presence of Polyphenols, Gallic tannins, Catechin tanninsand Flavonoids. These findings confirm that an 70 % ethanolic extract from Albizia lebbeck stem bark inhibited growth of Anti-methicillin resistant at low concentration and could be utilised as an alternative Anti-methicillin resistantagent.